The Role Of Performance And Work Motivation In Improving Employee Productivity At The Cirebon Regency Social Affairs Office - Rizka Nurul Aini; Siti Khumayah; Leni Rohida (ann4publisher@gmail.com, 2026)
The Cirebon Regency Social Services Agency, as the agency responsible for social welfare services, is required to perform at an optimal level in supporting its operational activities and services to the community. Performance policies in public organizations are not only related to planning, monitoring, reviewing, and/or awarding incentives, but also require human resources capable of effectively leveraging that performance. Based on this assessment, in-depth research is needed to understand the role of employee performance and motivation in enhancing productivity at the Cirebon Regency Social Services Agency. This study is expected to provide insights into the relationship between performance, work motivation, and employee productivity, as well as generate strategic recommendations to improve organizational performance. Based on the results of the research conducted at the Cirebon Regency Social Services Office, it was found that performance and work motivation are closely linked to enhancing employee productivity. Employee productivity in public organizations is influenced not only by individual ability to complete tasks but also by work motivation, the organizational environment, leadership support, and the work systems implemented within the organization. This study employed a qualitative approach using in-depth interviews, observation, and documentation. The primary informant in this study was the Head of the Cirebon Regency Social Services Office, while supporting informants consisted of civil servants (ASN) and non-civil servants (Non-ASN) directly involved in public service activities.